HUBUNGAN ANTARA HARGA DIRI DENGAN PERILAKU IMPULSIVE BUYING PADA REMAJA PENGGEMAR K-POP - Nafeesa Nafeesa; Eryanti Novita (Cakrawala - Jurnal Humaniora, 2021)
KPop is currently a trend for some teenagers. Most of these teenage Kpop fans feel that being a fan also has to collect various kinds of goods or what is commonly known as merchandise related to their idols. They assume that buying these items will make them true fans no matter what the price. They are willing to spend up to millions of rupiah to get their idol's original products such as albums, clothes, bags, pants, hats, bracelets and so on. Furthermore, this study will analyze the problem of high idol impulsive buying behavior in the adolescent community and determine the relationship between self-esteem and impulsive buying behavior in adolescents. This study will specifically examine whether there is a relationship between self-esteem and impulsive buying behavior in adolescents. This research will use Coopersmith's theory of self-esteem and Rook and Fisher's theory of impulsive buying, which is then examined in terms of its aspects and characteristics. Keywords : Teens, KPop Fans, Impulsive Buying, Self-Esteem